Modeling the Way: Strategi Pembelajaran Aktif untuk Meningkatkan Pemahaman Materi Optimis, Ikhtiar, dan Tawakal di Kelas IX SMP - Khofiyah, Siti (Nusantara: Jurnal Pendidikan Indonesia, 2023)
The implementation of learning requires effective and relevant learning to improve students' skills. This study aims to determine the effectiveness of the active learning strategy Modeling the Way in the learning process, especially in Islamic Religious Education and Moral Education learning on Optimistic, Endeavor, and Tawakal material. This research is a type of classroom action research. This study uses two cycles where each cycle consists of four stages: planning, implementing, observing and reflecting. Data collection techniques using observation techniques. While the data collection tool is in the form of observation sheets. The subjects of this study were class IX students at SMP N 1 Kesesi. The results of the study show that the active learning strategy Modeling the Way is effective to be applied in the learning process of Islamic Religious Education and Characteristics in Optimistic, Endeavor, and Tawakal material. This can be seen from the increased achievement of student learning outcomes from an average of 64.68 to 91.09.